Comparative Study of the Experiences of NHIS Subscriber and Non-Subscribers in Accessing Health Care at the Ga East Municipality - Noi, E.N.N. (University of Ghana, 2012)
The main objective of this study is to examine the impact of the NHIS on ensuring accessibility to quality health care in the Ga East Municipality, especially by the poor and under-privileged; and to assess whether comparatively, subscribers or non-subscribers get easier access to health care. To do this, a mixed method approach was adopted in data collection and analyses. Thus, a semi-structured questionnaire and an interview guide were employed for data collection. Quantitative data so collected was analysed using SPSS 18 while the qualitative data was analysed based on the emerging themes through colour coding. In all 208 health respondents were contacted for data- 200 for quantitative and 8 for qualitative. Findings have it that comparatively; NHIS subscribers have better access to quality formal health care than non-subscribers. Subscribers and their children under 18 years have access to free OPD services, laboratory services, some surgical services, consultation and dispensary services at public and some private health facilities. Non-subscribers would have to pay for all such services when seeking health care. Subscribers however, have to spend more waiting time, suffer verbal abuses, and at times, frowned at for using NHIS card rather than cash. Subscribers may also pay extra money to cover for extra drugs and services not covered in the scheme. Poverty and negative perceptions were realized as the major barriers to subscription to the NHIS. In view of the findings, it was recommended that the drug list and surgical operations list be expanded to cover many other common health conditions; health workers who discriminate against NHIS card holders should be sanctioned, and that the NHIA should settle claims by the service providers promptly. Finally, more health workers were to be produced to lessen the burden on the few available.
Thesis (MA) - University of Ghana, 2012